OPTIMALISASI KEAMANAN FIREWALL PADA INFRASTRUKTUR JARINGAN SMK IDN BOGOR - Yel, Mesra Betty; Mulyana, Dadang Iskandar; F, Joe Renaldy; Nurfaishal, Muhammad Dzaky; B, Muhamad Hasbi Toharudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
IDN Bogor Vocational High School, which was established in 2016, is known as one of the many schools that are involved in the academic, religious and IT-focused world, as its vision is "Wonder of IT Smart of Praying". Given the large number of IT activities both in terms of learning and administratively office data collection (Administration), of course the application of a Firewall on the network is one of the crucial things needed to facilitate the security and authenticity of data from teachers and students. The purpose of preparing this KKP report is none other than to help optimize Firewall configurations, both on Firewall devices and PCs/Laptops along with counseling strategies as preventive measures to avoid physical/social engineering hacking at SMK IDN Bogor. As we all know, cybersecurity issues cannot be taken lightly. Therefore, for the sake of the continuity and smooth running of school education activities, Optimization/Standardization of all segments or parts that use the network within SMK IDN Bogor is required.